PENGARUH FATHERLESS TERHADAP KARAKTER PESERTA DIDIK FASE E DI SMA N 02 SOLOK SELATAN - Wolvi Darwan Cahyani; Mori Dianto; Wira Solina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to find out: 1) Description of fatherless Students, 2) Description of Student Character, 3) the influence of fatherless on Student Character. This research uses a correlational quantitative descriptive research method. The population of this study is 30 people. Sampling technique using total sampling. The instrument used in this research is the questionnaire. Data analysis in this study is percentage and simple linear regression using SPSS 22.0. The results of this study show: 1 Fatherless in SMA N 02 South Solok is in a low category. 2) The character of the students at SMA N 02 South Solok is in the bad category. 3) There is a Fatherless Influence on the character of students at SMA N 02 South Solok with a low coefficient with a score of 32%. Based on the results of this research, it is recommended to students, to improve the role of fathers as guidance teachers for their children. Then on the character aspect, namely, moral knowing is able to understand or know about good morals, so that it can form a good character.